THE EFFECTIVENESS OF SONGS IN IMPROVING STUDENTS’ VOCABULARYMASTERY : Song, Teaching, Vocabulary - Wakary, Andreas; Olii, Sanerita T.; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to determine whether or not using songs as media may help students learn more vocabulary. The researcher employed experimental research design, a quantitative research technique, to carry out this study. A second grade class of ten students at SMP Anugrah Tondano served as the topic of this investigation. Pre-test and post-test served as the tool for gathering data. The exams consisted of a few essays and fill-in-the-blank lyrics. The results of this study revealed that the post-test's mean score (86) was greater than the pre-test's mean score's (41) average. It is possible to get the conclusion that using songs is successful.